Isolation of Bacteria Associated with Mastitis and Measuring Level of Lactoferrin in Cow's Milk - Mahmood Kh.Fahmi; Asst. Prof. Dr. Maher S. Owain; Prof. Heba Y. Khalaf (Scholars Digest Publishing, 2023)
The study was conducted in Salah al-Din Governorate in areas adjacent to the city of Tikrit to diagnose mastitis in cows using various physical, chemical and bacterial tests, study the factors that accompany the disease, identify the types of bacteria causing the disease, record the clinical signs of the disease, compare the accuracy of the tests among them, and determine sensitivity and resistance. Microbiology of antibiotics and knowledge of the relationship of lactoferrin concentration to clinical and subclinical mastitis This study included (50) cows, 40 of which suffered from clinical and subclinical mastitis, and 10 of which were healthy and showed no signs of infection. For the period from April 2022 to January 2023, vital signs and physical signs in the milk were recorded using special forms that were prepared in advance. For all animals. 50 ml of milk was collected from all quarters of the udder and placed in sterile tubes. Bacterial screening operations were performed on the samples and the concentration of lactoferrin was measured through the separation process and the whey was stored in the freezer at a temperature of -20°C until ELISA tests were performed on them to measure the concentration of lactoferrin in the milk serum. . a. The results of aerobic bacterial tests in cows showed that the total incidence of clinical and subclinical mastitis was (27.5%) and (72.5%), respectively. Bacteriological examinations were performed on all samples, and the gram-positive bacterial species were isolated from the milk. They were different in percentages, such as Coagulase negative Staphylococci, the most prevalent bacteria with a percentage of (42.23%): Staphylococcus intermedius 9.85%, Staphylococcus hyicus 23.94, Staphylococcus saprophyticus 1.40%, Staphyl epidermidids coccu 7.04 %, as for Staphylococcus aureus, the percentage was the highest (25.35%). Followed by Streptococcus spp, 9.85%. The prevalence of Gram-negative bacteria varied in percentages, such as Escherechia coli 12.67%, Proteus mirabilis 11.26%, Manheimia hemolytica 1.40%, Pseudomonas aeroginosa 4.22%, Pasteurella spp. 2.81%. The results of lactoferrin showed significant differences at the level (P>0.05) in the milk of cows suffering from clinical and subclinical mastitis, which had the highest concentration from healthy cows (control).
Keywords: physical, chemical and bacterial tests, study the factors that accompany the disease